Analisis Penyebab, Konsekuensi dan Solusi Potret Kemiskinan di Indonesia Pasca Era Reformasi - Ni Made Arsita Kusumadewi; Miftahul Hariz; Muhammad Yasin (Universitas 45 Surabaya, 2024)
Poverty is a major problem for countries throughout the world, developing countries themselves have a lot of poverty among their people. Poverty is a condition where a person cannot fulfill their basic needs such as clothing, food, shelter, health and education. One of the benchmarks for assessing the success of socio-economic development is poverty itself (Priseptian & Primandhana, 2022). The portrait of poverty in Indonesia's big cities is marked by the mushrooming of semi-permanent houses on riverbanks and along railway tracks. The portrait of poverty in post-reform Indonesia is at least reflected in the 2014 Human Development Index (HDI) data released by the United Nations Development Program (UNDP). The causes of poverty in Indonesia after the reform era are caused by internal and external factors. From the causes of poverty, a) unemployment, b) crime, c) dropping out of school, d) poor health, e) the next generation will emerge.